2015
DOI: 10.1016/j.proeng.2015.01.105
|View full text |Cite
|
Sign up to set email alerts
|

Wetting and Adhesive Forces on Rough Surfaces – An Experimental and Theoretical Study

Abstract: It is well known that wetting plays a crucial role in many processes due to its impact on the emerging adhesive forces. In general, high wetting angles between solid and liquid lead to higher adhesive forces and vice versa. For ideal systems the calculation of these adhesive forces is possible using analytical approaches for van der Waals and polar forces. But there is still a lack of knowledge how to consider impacts like roughness and irregular shape of the solids during the calculation.The present paper aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…There is no acceptable technique for estimating surface energy in a microscopic local area or on a separate NGs at present. The universal and accurate method of surface energy investigations is based on the assessment of the wettability of a surface 23 , 24 , but this allows us to estimate the total surface energy of the sample, but not a separate microscopic area or NG. The best contender for determining local specific surface energy is an atomic force microscope (AFM).…”
Section: Introductionmentioning
confidence: 99%
“…There is no acceptable technique for estimating surface energy in a microscopic local area or on a separate NGs at present. The universal and accurate method of surface energy investigations is based on the assessment of the wettability of a surface 23 , 24 , but this allows us to estimate the total surface energy of the sample, but not a separate microscopic area or NG. The best contender for determining local specific surface energy is an atomic force microscope (AFM).…”
Section: Introductionmentioning
confidence: 99%
“…A rougher surface provides an increased surface area and is known to increase reactivity. The detailed influence of the surface roughness on the filtration process is yet unknown and challenging to calculate due to complex interactions . Nevertheless, Voigt et al reported an increased filtration efficiency of rough filters for aluminum filtration.…”
Section: Discussionmentioning
confidence: 99%
“…Colloidal probe atomic force microscopy (CP-AFM) was first reported by [1,2] and is nowadays used in multiple applications in various fields of research. One possible application are adhesive force mappings on a variety of samples including biological [[3], [4], [5]], mineral [6,7], ceramic [[8], [9], [10]] or wooden samples [3,11]. Beside possible sources of contamination during storing in ambient conditions as summarized by [12], the main source of colloidal probe contamination in an adhesive force mapping application on mineral surfaces experienced by the authors are inorganic particulate contaminations [13], as given in Fig.…”
Section: Methods Detailsmentioning
confidence: 99%
“…A variety of methods for cantilever or colloidal probe functionalization have been reported in literature, the same applies for possible colloids attached to the cantilever like glass spheres [18], polystyrene particles [6,7,19], silica microspheres [14,19,20] Al 2 O 3 particles [[8], [9], [10]] or gold particles [14]. A broader overview of the colloidal probe method was compiled by [18], listing more possible probes like TiO 2 , MgO, ZnS, poly-(methyl methacrylate) and polyethylene.…”
Section: Methods Detailsmentioning
confidence: 99%
See 1 more Smart Citation